Occurrence of Three Haplotypes of Linepithema micans (Forel) (Hymenoptera: Formicidae) in Southern Brazil - Martins, C.; Nondillo, A. [UNESP]; Martins, V. G.; Botton, M.; Bueno, O. C. (Entomological Soc Brasil, 2012)
Linepithema micans (Forel) (Hymenoptera: Formicidae) is reported to occur from eastern Brazil to central Argentina in pasture or grassland, forest and second growth riparian forest, nesting under stones, rotting wood, and sandy soil. However, information on this species is poor and its ecological interactions and role as pests are unknown. Linepithema humile (Mayr), a closely related species to L. micans, known as the Argentine ant, is native to South America, and was accidentally introduced to several regions of the world. Recent studies have shown that other related species, such as L. micans, could become as pestiferous as L. humile because of its phylogenetic proximity. Samples of L. micans from different habitats in Southern Brazil were characterized by sequencing of the mitochondrial DNA. Sequences were compared to previously obtained sequences from samples of L. humile and the genetic distance and differences in the tRNALeu structure were investigated. Our data identified three haplotypes of L. micans, two of which were observed in ant populations closely associated with the Brazilian ground pearl Eurhizococcus brasiliensis (Hempel) (Hemiptera: Margarodidae), a soil scale that is a serious pest of vineyards. The third haplotype was identified in ants from populations invading residences in urban habitats.
Keywords: Linepithema; mtDNA; vineyards; ground pearl; mutualistic association